(3ehLR GdHjGf Yf GdeSGFd GdKeGfs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj JfLM YfOg GdeSGFd hJMd HJhajbg YbO GdeTGcd (B... (3CeG HYO, agPG ehLR GdHjGf Yf CLhHI GdeSGFd GdKeGf SFdfj YfgG HYV Cgd GdYde hGdJMUjd WGdHG GdETGQIs
(3BNQgG (B:s
(3BNQgG(B: (3hGdeSjMjhf bO GcKQhG ef GSJYeGd Pdc hef GSJYeGd GdhdO hGdehdhO aj GdeSjM Ydjg GdSdGe, hgh aj ZGjI GdUQGMI aj EOGQI Pdc GdeYfi GdaGSO hjbhdhf Ef GdYPQGA MHdJ hhdOJ hdkOG GSeg YGfhjd JYGdi Gddg Yf Pdc YdhG cHjQGs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis